Модифікований ресурсоекономний штучний камінь для виробництва архітектурного декору і стінових виробів на основі гіпсової в'яжучої речовини - Тарасевич, Віталій; Гасан, Юрій; Дроздова, Ольга (My University, 2020)
В статті наведено результати досліджень модифікування штучного гіпсового каменю розробленим гідрофобізуючим хімічним розчином на основі полісульфіду кальцію та діоксиду титану. Наведено порівняльні показники водопоглинання вихідних і просочених розчином зразків. Досліджені характеристики вихідних матеріалів. Показано, що гідрофобізація розробленим хімічним розчином, залежно від кількості нанесених шарів чи часу просочення, має високі показники коефіцієнту розм’якшення виробів, який знаходиться в межах 0,6…0,82. The article presents the results of studies of modification of artificial gypsum stone developed by a hydrophobic chemical solution based on calcium polysulfide and titanium dioxide. The comparative indices of water absorption of the initial and impregnated samples are given. The characteristics of the starting materials are given. It is shown that the hydrophobization of the developed chemical solution, depending on the number of applied layers or the time of impregnation, has a high coefficient of softening of the products, which is in the range of 0.6...0.82. The dependence of the change in the weight of the samples and the depth of penetration of the solution in the structure of gypsum stone on the number of layers of the coating is shown. The depth of impregnation was determined by splitting the specimens. It is shown that the aggregate increases strength, and the aggregate is selected according to the purpose of the products: wall and architectural decoration elements.
Keywords: гіпсовий камінь; в’яжучі; діоксид титану; сірка; просочення; Gypsum stone; binder; titanium dioxide; sulfur; impregnation